Factors Influencing Tenure Choice in European Countries - Monika Bazyl (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Homeownership rates are very different across European countries. They range from below 50% in Germany to over 80% in Greece, Spain or Ireland. However the differences lie not only in the overall homeownership rates but also in its structure, and this is the focus of this paper. Its aim is to study the impact of microeconomic factors on household's tenure choice, using a cross-country comparative approach. Logit models are constructed for each country using data for year 2000 from the Consortium of Household Panels for European Socio-Economic Research micro-database. The models show that marriage is a significant determinant of the decision to move to homeownership in all analysed countries, while co-habitating households are more likely to rent, except for Denmark. Nationality, income and age proved to be significant explanatory variables in several countries, while staying insignificant in others.
Keywords: D10; R20; 330; Tenure choice; homeownership; housing